Analisis Tingkat Kepuasan Konsumen Terhadap Kualitas Produk Dan Kualitas Pelayanan Mie Gacoan Di Kota Jambi - Ary Dean Amry; Rahmad Irawan; Aldi Fitriyanto; Dharil Ihsan Alvarabi; Willy Yuda Al Faroq; Iqbal Alfansyuri (JOURNAL OF SHARIA ECONOMICS, 2024)
The purpose of this research is to determine the influence of product quality and service quality on the level of consumer satisfaction of Mie Gacoan in Jambi City. This research method uses quantitative research methods. The population in this study was 50 consumers. Multiple regression is used for hypothesis testing. The research results show that there is a significant influence between service quality and consumer satisfaction. However, product quality has not been able to prove a relationship to customer satisfaction. Implications and suggestions are explained in the article.